Insects and SARS-CoV-2: Analysis of the Potential Role of Vectors in European Countries - Dutto, M.; Lauria, G.; Drago, A.; Martini, S.; Gorrasi, I.; Gilli, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
SARS-CoV-2 is a coronavirus responsible for the pandemic that developed in China in late 2019. Transmission of the virus is predominantly direct, through exposure to infected respiratory secretions. As far as we know, arthropods play a key role in the transmission and spread of several viruses, and thus their role in the spread of COVID-19 deserves to be studied. The biological transmission of viral agents through insects is very complex. While mechanical transmission is more likely to happen, biological transmission is possible via blood-sucking arthropods, but this requires a high grade of compatibility between the vector and the pathogen. If the biological and mechanical transmission of SARS-CoV-2 by blood-sucking arthropods is excluded, a mechanical transmission by urban pests could take place. This risk is very low but it could be important in isolated environmental conditions, where other means of transmission are not possible. The presence of SARS-CoV-2 in non-blood-sucking arthropods in infected buildings, like hospitals and retirement homes, should be investigated.